Gamified digipuzzle-based instruction to support early reading development in elementary learners - Handayani, Tri; Chamalah, Evi; Kusumadewi, Rida Fironika; Muliasari, Desiani N; Silawati, Endah (Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading is a foundational competency in early-grade education; however, many students experience delays in developing basic decoding and comprehension skills. This study aims to examine the effect of gamified learning using the Digipuzzle application on the reading skills of first-grade students at SDN Sukajaya 2. A quantitative one-group pretest–posttest design was employed involving 25 students. Reading performance was measured using a structured assessment administered before and after the intervention. The results indicate that the mean pretest score increased from 50.12 to 75.76 in the posttest. Statistical analysis using a paired-sample t-test confirmed a significant difference between the two measurements (p = 0.000 < 0.05). The gain analysis produced an average N-gain score of 0.486, indicating a moderate level of improvement. These findings demonstrate that integrating gamification through Digipuzzle is associated with measurable gains in early reading performance. This study provides empirical evidence supporting the use of game-based digital media as an instructional strategy to enhance foundational literacy skills in primary education.